Intraosseous Administration of Tissue Plasminogen Activator on a Mobile Stroke Unit. (4th July 2019) - Bowry, Ritvij; Nour, May; Kus, Teresa; Parker, Stephanie; Stephenson, Jonathan; Saver, Jeffrey; Grotta, James C.; Ostermayer, Daniel
Abstract: Objective: Mobile stroke units offer improved time to administration of thrombolytics for ischemic stroke patients. Acquisition of intravenous (IV) access, however, can be challenging in the prehospital environment leading to treatment delays. Intraosseous (IO) access is commonly used in the prehospital setting for a variety of conditions and may serve as a viable means for tPA (tissue plasminogen activator) administration.Methods/Results: We describe 3 cases in which tPA was administered via IO access on a mobile stroke unit as part of the Benefits of Stroke Treatment Delivered Using a Mobile Stroke Unit Compared to Standard Management by Emergency Medical Services (BEST-MSU) trial.Conclusion: No adverse events were observed in the process of obtaining IO access or administering tPA.